Internal efficiency of our lady of assumption school san pedro, laguna: basis for school plan - Samaniego, Mercy D. (San Miguel, Iriga City: University of Saint Anthony, 2001)
Internal efficiency of our lady of assumption school san pedro, laguna: basis for school plan.
Includes bibliographical references.
English
Keywords: School plan